A New Era of Integrative Ice Frozen Assembly into Multiscale Architecturing of Energy Materials. (11th February 2022) - Yeon, Jeong Seok; Gupta, Nisha; Bhattacharya, Pallab; Park, Ho Seok
Abstract: The ice templating assembly has been investigated to construct macroporous channels of functional nanomaterials with well‐defined homogeneous morphology. Recently, this templating method has been revisited integrating with other materials' synthesis and processing methodologies (such as, spinning, spraying, filtration, hydrothermal, oxygenation, gelation, and 3D printing) for electrochemical energy conversion and storage applications. Herein, the recent progress on "integrative ice frozen assembly" focusing on the hierarchical structures and chemistries of functional nanomaterials such as, organic, inorganic, carbon, and composite materials for a rational design of energy application‐oriented materials is comprehensively reviewed. This integrative process allows functional nanomaterials to be assembled into various dimensions, such as, 0D, 1D, 2D, and 3D macrostructures, as well as, into larger bulk objects such as, fibers, films, monoliths, and powders. The fundamental understanding of the integrative ice frozen assembly is thermodynamically and kinetically discussed with the help of primitive freeze casting domain knowledge and the energy conversion and storage performances of the as‐designed electrodes with their hierarchical structures and chemistries are further correlated. The applications of the as‐assembled electrodes into batteries, supercapacitors, fuel cells, and electrocatalysis are also addressed. Finally, the perspective on the current impediments and future directions in this field is discussed. Abstract : The recent progress on "integrative ice frozen assembly" is comprehensively reviewed focusing on the hierarchical structures and chemistries of functional nanomaterials and their correlations with energy conversion/storage performances.